Stability Optimization of Trapezoidal Frame with Rigid Members and Flexible Joints - He, Li; Tam, Lik-Ho; Li, Ya-Nan; Wu, Chao (Advances in Civil Engineering, 2020)
Stability has been an important subject in the design of a portal frame structure. Conventional stability analysis of the portal frame is normally conducted assuming that all the joints are rigid. However, the joints of a portal frame in real applications are not always rigid and semirigid connections often exist. AISC design code requires that the effect of the joint flexibility on the behavior and buckling capacity of the portal frame should be taken into account in the analysis and design procedures. To address this issue, a portal frame with flexible joints and rigid members was theoretically analyzed in the literature and closed form solution was derived for its global buckling load. However, when more parameters are involved, e.g., different leg lengths, asymmetric frame shape, and moving load, the solution to the governing equation of the stability of the frame becomes impossible. This paper presents a comprehensive parametric study on the stability of an asymmetric portal frame with flexible joints and rigid members through finite element (FE) analysis. The FE model was first validated by the existing theoretical solution in the literature. Parameters including the position of the moving load, the lengths of the two frame legs, and the span of the frame were analyzed. Design curves were developed based on the parametric study, from which the stable, unstable, and catastrophically unstable states of the portal frame were characterized. This paper contributes benchmark results for the stability optimization in the design of the portable frame of a general shape.